2005
DOI: 10.1007/s11095-005-7096-0
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Cell Proliferation by Inhibition of Estrone-3-Sulfate Transporter in Estrogen-Dependent Breast Cancer Cells

Abstract: The uptake of estrone-3-sulfate is mediated by Na+-independent transporter(s). Inhibitor of estrone-3-sulfate transporter suppressed the transcription and cell proliferation induced by estrone-3-sulfate in MCF-7 cells. The results provide the basis of a novel strategy for breast cancer treatment by focusing on the transporter responsible for the uptake of estrone-3-sulfate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…6), hepatocellular carcinomas (11), breast carcinomas (13), and lung cancer (12). In addition, expression of OATP1B1 and OATP1A2 was found in malignant breast cell lines (14,43), and OATP1A2 (and OATP2B1) have also been localized in the blood-tumor barrier of gliomas (44). Recently, Takano and colleagues (2009) have shown in vitro that hepatoma cells made resistant to paclitaxel treatment showed, besides increased P-glycoprotein expression, drastically decreased mRNA expression of SLCO1B3 (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6), hepatocellular carcinomas (11), breast carcinomas (13), and lung cancer (12). In addition, expression of OATP1B1 and OATP1A2 was found in malignant breast cell lines (14,43), and OATP1A2 (and OATP2B1) have also been localized in the blood-tumor barrier of gliomas (44). Recently, Takano and colleagues (2009) have shown in vitro that hepatoma cells made resistant to paclitaxel treatment showed, besides increased P-glycoprotein expression, drastically decreased mRNA expression of SLCO1B3 (45).…”
Section: Discussionmentioning
confidence: 99%
“…9), and in small intestine (10), where its effect on drug absorption and/or elimination needs further investigation. Besides their physiologic expression, many OATPs have been found expressed in certain malignancies like breast, gastrointestinal, and lung cancers (6,(11)(12)(13)(14), where they may well be involved in the tumor uptake of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to investigate transcript and protein expression of seven OATP isoforms that recognize E3S as a substrate and further evaluate their differential functional role in E3S uptake among immortalized breast epithelial cells, hormone-dependent breast cancer cells, and hormone-independent breast cancer cells. Although previous work reported OATP expression in hormone-dependent breast cancer cells (MCF7, T47D, and ZR75) (Nozawa et al, 2004(Nozawa et al, , 2005Maeda et al, 2010), for the first time, we compared OATP expression and function in immortalized breast epithelial cells (MCF10A), hormone-dependent breast cancer cells (MCF7), hormoneindependent, invasive, and metastatic breast cancer cells (MDA435/LCC6, derived from MDA-MB-435 cells) (Leonessa et al, 1996), hormone-independent and epidermal growth factor receptor overexpressing breast cancer cells (MDA-MB-468) (Armstrong et al, 1994), and triple negative breast cancer cells (MDA-MB-231) (Grü ndker et al, 2010). Confirmed differences in OATP expression between these cell lines may aid in elucidating the basis for the high tumor concentrations of E3S reported in postmenopausal patients with hormone-dependent breast cancers.…”
Section: Introductionmentioning
confidence: 91%
“…This suggests that OATPs are involved in E3S uptake by breast cancer cells. Furthermore, Nozawa et al (2004Nozawa et al ( , 2005 showed that inhibition of an E3S transporter results in the suppression of hormone-dependent breast cancer cell proliferation (MCF7 and T47D cells). These data suggest a potential role of OATPs in hormone-dependent breast cancers proliferation by facilitating E3S cellular uptake.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological roles of these transporters are not yet fully understood, but there is compelling evidence that certain members of the OATP family promote cell proliferation and survival of human malignant tissues. We have previously shown that transport of estrone 3-sulfate via OATPs sustains the growth of hormone-dependent human breast cancer cells [7,8], because estrone-3-sulfate can be hydrolyzed by steroid sulfatase (STS) to estrone and eventually estradiol. We recently showed that OATP1B3 contributes to estrone 3-sulfate uptake in estrogen receptor-positive human breast cancer MCF-7 cells [9].…”
Section: Introductionmentioning
confidence: 99%